Um curso de Física aplicado à educação escolar indígena - Silva, Francisco Américo da (2016)
The aim of this work was to investigate the potentiality of the Didatic Guide, Applied Physics to the environment, as a methodological resource facilitator of meaningful learning. Focused on Indian Teacher Training on Mathematics and Natural Science, the research was developed during the use of the Guide into the subject “Applied Physics to the environment”, with a workload of 60 hours, of the Indigenous Intercultural Degree Course, offered by Mato Grosso University, in the second semester of 2015, with the purpose of verifying its applicability and to find evidences of meaningful learning. In the methodological proposal the concepts of air temperature, air relative humidity, precipitation and solar radiation are presented into the perspective of The Theory of Conceptual Fields from Vergnaud, relating them to the environment aspects and to indigenous culture. The data was collected through questionnaire, interviews, record of experimental activities, photographs and written test. 11 students from different ethnicities took part of this survey, whose reports were systematized, categorized, compared and analyzed, on the problem solving, following the triplet: Situations, Operative invariants and Symbolic Representation. The analysis realized showed that the proposal was well received by the participants and it did not cause any estrangement to the content developed in the subject, and also showing some evidences of meaningful learning.